How Can Pesantren Curriculum Development Keep up with Society's Needs for Life Skills Education? - Fadlin, Iswan; Hendra, Hendra; Uzunboylu, Mehmet (Islamic Educational Management Programme, 2024)
This study examines the development of life skill curricula in Islamic boarding schools from a qualitative perspective, concentrating on planning approaches, curriculum integration with extracurricular activities, and implementation strategies. This is a qualitative study employing descriptive survey methods. The investigation was conducted at several modern Islamic boarding schools (Pesantren) in the Aceh province, including Pesantren AlMuslim Bireuen Pesantren and Dayah Ruhul Qurani Meulaboh. The result shows monitoring and evaluation processes and examines the role of community collaboration and continuous teacher performance improvement in light of the importance of holistic development. The insights derived from this discourse can potentially inform and enhance education policies, fostering the desirable life skills within pesantren organizational settings. Life skill curriculum development in Islamic boarding schools adopts a bottom-up planning approach, accommodating the needs of graduates and institutions while integrating the national curriculum with extracurricular values and activities. Implementation occurs through lectures, counseling, soft skill enrichment, and boarding school activities. Monitoring and evaluation are performed internally and externally, aiming to develop life skills rooted in monotheism, Sharia, and noble character.